Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1186/1475-2875-6-40
|View full text |Cite
|
Sign up to set email alerts
|

Choice of treatment for fever at household level in Malawi: examining spatial patterns

Abstract: Background: Although malaria imposes an enormous burden on Malawi, it remains a controllable disease. The key strategies for control are based on early diagnosis and prompt treatment with effective antimalarials. Its success, however, depends on understanding the factors influencing health care decision making at household level, which has implications for implementing policies aimed at promoting health care practices and utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 27 publications
10
41
1
Order By: Relevance
“…In addition, those with private health facilities that are close cannot also afford the services, hence, resort to the traditional healer who most of the time operates next door or is willing to offer services to the sick in the person's house. This is consistent with the findings of Kazembe et al, (2007) who reported that the treatment choices for fever are related to the place of residence in Malawi. The results however further indicate that rural residents with health insurance are less likely to use traditional medicine compared to the government health facilities.…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, those with private health facilities that are close cannot also afford the services, hence, resort to the traditional healer who most of the time operates next door or is willing to offer services to the sick in the person's house. This is consistent with the findings of Kazembe et al, (2007) who reported that the treatment choices for fever are related to the place of residence in Malawi. The results however further indicate that rural residents with health insurance are less likely to use traditional medicine compared to the government health facilities.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…This result is not very surprising in the context of a developing country like Ghana where some of the older people still believe in the use of traditional medicine compared to orthodox medicine for the treatment of diseases. This concurs with the findings of Kazembe et al, (2007) reporting that the treatment options are related with the age of the mother/care-giver.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…This confirms the findings that poly-pharmacy is a common practice in Ghana [6,7]. Previous studies report similar findings in other countries [8]. This finding brings to light the importance of home management programmes where communities will be allowed to manage fever cases through the services of community volunteers trained by the health sector to diagnose and administer appropriate treatment while referring more complicated cases to health facilities.…”
Section: Discussionsupporting
confidence: 88%
“…Besides, households who watched television at least once in a week and those who have used a health facility at least once in a year are more likely to use modern health care compared to traditional or no care [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that children with fever in Malawi are often treated at home (Kazembe, Appeleton and Kleinschmid 2007;Holtz et al 2003). According to Ministry of Health protocols, hotline workers only refer children with a fever to the nearest village clinic or health center for diagnosis and treatment if the fever is being presented as a danger sign and has persisted for seven days or if the fever is accompanied by other symptoms.…”
Section: Child Healthmentioning
confidence: 99%